SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU DI SMA NUR EL-FALAH KUBANG MENGGUNAKAN FRAMEWORK CODEIGNITER - Hendra, Yul; Usman, Andi usri; Juniansha, Dedi; Ruhiawati, Irma Yunita (Jurnal Sistem Informasi dan Informatika (Simika), 2024)
Nur-Elfalah High School currently registers new prospective students manually, namely by coming directly to the school and filling out the registration form. In this way, sometimes queues often occur during registration, and when finding out initial information about parents or prospective students. having to spend time coming in person, this is considered less effective. Nur-Elfalah's New Student Admission (PPDB) is designed to be web-based using an internet network, prospective new students can view information related to the school online, can register online, making it easier to register and view information. Apart from that, by implementing the PPDB system, all registration data will be stored neatly in a database so that if necessary it is easy to search and display in report format. In designing the Information System for accepting new students (PPDB), the waterfall development method is used, where the system is developed in stages and continues to be refined on an ongoing basis. With the new student admission information system (PPDB), it is hoped that it will make it easier for prospective new students to view information and register at the Nur-Elfalah school. It is hoped that prospective new students can register easily anywhere and at any time, as long as the prospective students Just able to access the internet. By implementing this system, it is hoped that it will be able to help Nur-Elfalah school improve its services which will indirectly have an impact on increasing the number of prospective students